Monoclonal Antibodies That Recognize the Alkylation Signature of Antimalarial Ozonides OZ277 (Arterolane) and OZ439 (Artefenomel) - Jourdan, Joëlle (ACS Infect Dis, 2015)
[Image: see text] The singular structure of artemisinin, with its embedded 1,2,4-trioxane heterocycle, has inspired the discovery of numerous semisynthetic artemisinin and structurally diverse synthetic peroxide antimalarials, including ozonides OZ277 (arterolane) and OZ439 (artefenomel). Despite the critical importance of artemisinin combination therapies (ACTs), the precise mode of action of peroxidic antimalarials is not fully understood. However, it has long been proposed that the peroxide bond in artemisinin and other antimalarial peroxides undergoes reductive activation by ferrous heme released during hemoglobin digestion to produce carbon-centered radicals that alkylate heme and parasite proteins. To probe the mode of action of OZ277 and OZ439, this paper now describes initial studies with monoclonal antibodies that recognize the alkylation signature (sum of heme and protein alkylation) of these synthetic peroxides. Immunofluorescence experiments conducted with ozonide-treated parasite cultures showed that ozonide alkylation is restricted to the parasite, as no signal was found in the erythrocyte or its membrane. In Western blot experiments with ozonide-treated Plasmodium falciparum malaria parasites, distinct protein bands were observed. Significantly, no protein bands were detected in parallel Western blot experiments performed with lysates from ozonide-treated Babesia divergens, parasites that also proliferate inside erythrocytes but, in contrast to P. falciparum, do not catabolize hemoglobin. However, subsequent immunoprecipitation experiments with these antibodies failed to identify the P. falciparum proteins alkylated by OZ277 and OZ439. To the best of the authors’ knowledge, this shows for the first time that antimalarial ozonides, such as the artemisinins, alkylate proteins in P. falciparum.